Community Decision Support Service System Village Level Mandiri Based on an Interactive Website - Agung Yuliyanto Nugroho (STIKes Ibnu Sina Ajibarang, 2023)
Every village is required to provide the best possible service to the community in the areas of writing letters, population data collection, and other needs related to village office services. The process still requires residents to come and follow the procedures to get the letter. In this case, the letter cannot be processed in one day because often the village head who is authorized to sign the letter is not there because he is on assignment out of the area. So wait for the next day or wait for a confirmation Wats app from the Kadilangon village administration department to come and pick up the letter that has been processed. This process requires more time to carry out and obtain services and documentation of letters submitted by Kadilangon village residents. The process of serving letters submitted online is to make it easier for residents in terms of the application process and for employees themselves to make the documentation and report letter process easier. The author created a community service information system in Kadilangon village. In this system, residents can apply for letter permits online. It is hoped that this will make the letter application process faster and easier because the system can be accessed from anywhere. With this community service system, it is hoped that it can improve the quality of the service process to the people of Kadilangon village.